A swing arm device for the acoustic measurement of food texture. Issue 2 (12th December 2018) - Akimoto, Hidemi; Sakurai, Naoki; Blahovec, Jiri
Abstract: We developed a swing arm device for acoustic measurement of food texture, which resolved difficulties of food texture evaluation. The device has a structure of balance‐style and a probe in the device is moved downward along with motion of swing arm according to the balance of weights at both ends of the swing arm. The probe was inserted into a food sample. The device measured displacement and acceleration of the probe on food fracture by probe insertion with high precision until the probe stops inserting into a food sample. Using the displacement and acceleration of the probe on fracture, we calculated three parameters to determine food texture. Energy texture index (ETI) which is probe kinetic energy of acoustic vibration was evaluated by the vibration on food fracture. Audible energy texture index (aETI) could be introduced as food texture perceived by human sense of hearing, which was obtained by multiplying ETI by human hearing sensitivity. It was found that the ETI and aETI can be used for measurement of characteristic food texture detected at a tooth and perceived in brain, respectively. Food friction index (FFI) to explain the friction strength of a probe against a food sample was theoretically formulated under the condition of probe motion in the device. FFI was found to be useful not only for crispy food like biscuit but for soft food. The measured FFI indicated characteristic of smoothness of probe insertion into food sample. Practical applications: The swing arm device can be used to estimate food texture by measuring probe vibration energy on food fracture. Energy texture index (ETI) and Audible energy texture index (aETI) are introduced into measurements of food with crispness which emits sounds on fracture by probe insertion. ETI is an index to estimate probe vibration energy, while aETI is one to estimate food texture by human sense of hearing that was corrected by human hearing sensitivity as human hearing sensitivity is highest around sound frequency ranging from 1, 000 to 4, 000 Hz. Food friction index (FFI) was also obtained by the device to evaluate smoothness of probe insertion into a food sample. ETI, aETI, and FFI can be useful parameters for food texture of water melon, pear, persimmon, apple, cookie, potato chips, and biscuit. FFI is especially suitable for evaluation of soft food such as banana, avocado, mango, melon, peach, pudding, or bread.